In Vitro Evaluation of Flexural Strength, Impact Strength, and Surface Microhardness of Vaccinium macrocarpon Reinforced Polymethyl Methacrylate Denture Base Resin - Anitha Kuttae Viswanathan; Rajkumar Krishnan (Clinical and Experimental Dental Research)
ABSTRACT Objective The antimicrobial efficacy of cranberry (CA) against oral infections was well evidenced. Influence of cranberry on the mechanical properties of heat‐activated polymethyl methacrylate (HA‐PMMA) denture base resin (DBR) is unexplored till date and is significant for a better understanding of the reinforcement. This study aimed to evaluate the flexural strength (FS), impact strength (IS), and surface microhardness (VHN) of heat‐cure PMMA DBR reinforced with varying concentrations of Vaccinium macrocarpon (cranberry) extract. Material and Methods A total of 150 samples were categorized into five groups (n = 10) by weight percentage of 0, 0.5, 1.0, 1.5, and 2.0 cranberry extract added into HA‐PMMA polymer after the performance of antimicrobial efficacy testing of CA. Three‐point bending test for FT, Izod impact testing for IS, and Vickers microhardness test were performed. Fractured sample surface was characterized by a high‐resolution scanning electron microscope (HR‐SEM). Raw data were statistically analyzed with one‐way ANOVA and post hoc Bonferroni test. Results A significant improvement in flexural strength of 76.88 ± 0.73 MPa, impact strength of 6.66 ± 0.24 kJ/m2, and microhardness of 18.44 ± 0.27 kg/mm2 was observed at 2 wt.% (p < 0.0001). Fractured surface topography showed dispersion of cranberry particles as a thin fibrous band intermeshed within resin matrix. Conclusions Addition of up to 2 wt.% cranberry improved the FS, IS, and VHN on comparison to 0 wt.% control HA‐PMMA.